1994
DOI: 10.1073/pnas.91.25.12120
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of nucleotide interactions of BiP and GTP-binding proteins.

Abstract: BiP is a member of the Hsp7O heat shock protein family found in the lumen of the endoplasmic reticulum, that binds to a variety of proteins destined to be secreted. Substance P (SP) has been used as a model peptide to study the interaction of BiP with protein substrates. SP stimulates BiP ATPase activity and forms a stable complex with BiP that is dissociated in the presence of levels of ATP > 50 pM. At lower concentrations of ATP, the SP remains bound to BiP, and the results are consistent with the view that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…In contrast to the in vivo study by Freiden et al (1992), two of these studies found evidence for peptide binding to polymerized BiP in vitro (Blond-Elguindi et al, 1993;Brot et al, 1994). Unfortunately, these two studies disagree with each other in major respects.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…In contrast to the in vivo study by Freiden et al (1992), two of these studies found evidence for peptide binding to polymerized BiP in vitro (Blond-Elguindi et al, 1993;Brot et al, 1994). Unfortunately, these two studies disagree with each other in major respects.…”
Section: Discussionmentioning
confidence: 47%
“…Blond-Elguindi et al (1993) found that neither recombinant BiP nor BiP prepared from liver were depolymerized at low concentrations of ATP, although peptide depolymerized BiP. On the other hand, Brot et al (1994) found that low concentrations of ATP depolymerizes BiP almost completely, although peptide binding had no effect on the amount of polymer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such example may be the interaction of chaperons, such as the hsp 70 family, with malfolded proteins and adenosine nucleotides. Although ATP and ADP are involved in these reactions, and not guanosine nucleotides, it is quite easy to formulate a series of reactions with similarities to those seen with G proteins (Brot et al, 1994).…”
Section: Guanosine Nucleotide Binding In Animal Cellsmentioning
confidence: 99%